The relationship between serum vitamin D, testosterone, and oxidative stress levels in women with sexual dysfunction: A case-controlled study - Mohammadreza Rafati; Elahe Bazrafshan; Fatemeh Shaki; Tahereh Ghalini-Moghaddam; Minoo Moghimi (Elsevier, 2024)
Objective: Female sexual dysfunction (FSD) is highly prevalent and can result from hypovitaminosis D. Besides the role of vitamin D in normal bone development, studies showed it could reduce oxidative stress and lipid peroxidation. This prospective study aims to evaluate the relationship between serum vitamin D, testosterone, and oxidative stress levels in women with FSD. Materials and methods: In this cross-sectional study, a total of 40 women with FSD (age range: 18-45 years) were randomly assigned into two groups of intervention and control. In the intervention group, patients received vitamin D 300,000 IU intramuscularly (IM) and then 50,000 IU orally once a week for four weeks. We measured the serum vitamin D, testosterone, and oxidative stress levels, as well as the Female Sexual Function Index (FSFI) at baseline and monthly for three months. Results: Serum testosterone levels significantly increased in the intervention group at the end of the third month (P = 0.014). Also, FSFI scores significantly improved (P < 0.01) in the intervention group compared to the control group. While there was positive a correlation between serum vitamin D levels with glutathione, total antioxidant capacity (TAC), testosterone, and FSFI score, there was a negative correlation between serum vitamin D levels with malondialdehyde (MDA), protein carbonyl, and nitric oxide. Conclusion: We witnessed that women with FSD had low serum vitamin D levels. So, modifying serum vitamin D levels must be considered as a treatment option. Moreover, vitamin D supplementation improved testosterone, serum oxidative stress, and sexual function.